Epidemiology, Clinico-Pathological Characteristics, and Comorbidities of SARS-CoV-2-Infected Pakistani Patients - Omer, Saadia; Gondal, Mehrunnisa Fatima; Usman, Muhammad; Sarwar, Muhammad Bilal; Roman, Muhammad; Khan, Alam; Afzal, Nadeem; Qaiser, Tanveer Ahmed; Yasir, Muhammad; Shahzad, Faheem; Tahir, Romeeza; Ayub, Saima; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
SARS-CoV-2 is a causative agent for COVI-19 disease, initially reported from Wuhan, China. Infected Patients experienced mild to severe symptoms, resulting in several fatalities due to a weak understanding of its pathogenesis, which is the same even to date. This cross-sectional study has been designed on four hundred and fifty-two symptomatic mild-to-moderate and severe/critical patients to understand the epidemiology and clinical characteristics of COVID-19 patients with their comorbidities and response to treatment. The mean age of studied patients were (58±14.42) years, and the overall male to female ratio was 61.7 to 38.2%, respectively. 27.3% of the patients had a history of exposure, 11.9% travel history, while for 60% of patients, the source of infection was unknown. The most prevalent signs and symptoms in ICU patients were dry coughs, myalgias, shortness of breath, gastrointestinal discomfort, and abnormal Chest X-ray (p<0.001), along with the high percentage of hypertension (p=0.007) and COPD (p=0.029) as leading comorbidities. Complete Blood Counts indicators were significantly disturbed in severe patients, while the Coagulation Profile and D-dimer values were significantly higher in mild-to-moderate (non-ICU) patients (p < 0.001). Serum Creatinine (1.22 umole L-1; p = 0.016) and LDH (619 umol L-1; p < 0.001) indicators were significantly high in non-ICU patients while, raised values of Total Bilirubin (0.91 umol L-1; p = 0.054), CRP (84.68 mg L-1; p = 0.001) and Ferritin (996.81 mg L-1; p < 0.001) were found in ICU patients. Drug Dexamethasone was the leading prescribed and administrated medicine to the COVID-19 patients, followed by Remdesivir, Meropenem, Heparin, and Tocilizumab, respectively. A characteristic pattern of Ground glass opacities (GGO), consolidation, and interlobular septal thickening were prominent in severely infected patients. These findings could be used for future research, control, and prevention of SARS-CoV-2 infected patients.